التوزيع الأوركسترالي لأعمال جون وليامز من خلال موسيقى فيلم هاري بوتر - الشامي، أيمن يوسف علي حسن (جامعة حلوان - كلية التربية الموسيقية, 2020)
يعتبر جون ويليامز هو أجد الموسيقيين البارعين في مجال الموسيقى التصويرية حيث أنه حاز على خمس جوائز الأوسكار، أربع جوائز غولدن غلوب، سبع جوائز الأكاديمية البريطانية للأفلام، و23 جوائز جرامي. مع ٥٠ ترشيحات لجوائز الأوسكار لذلك يعتبر وليامز هو ثاني شخص الأكثر ترشح، بعد والت ديزني. كان هاري بوتر وحجر الفيلسوف (أو في الولايات المتحدة وهاري بوتر وحجر الساحر) الأول في سلسلة من الروايات الخيالية السبع التي تؤرخ مغامرات الساحر الشهير هاري بوتر مع قوى الشر من الطفولة إلى سن الرشد، أطلقت الرواية في عام ١٩٩٧، وأشعلت خيال المشجعين لا تعد ولا تحصى والروايات السبع معا باعت أكثر من ٤٥٠ مليون نسخة حتى الآن، مما يجعل هاري بوتر سلسلة الكتب الأكثر مبيعا في التاريخ. تعد الموسيقى التصويرية أو الساوند تراك بالإنجليزية (sound track)، هي المعادل المسموع للمشهد السينمائي أو المسرحي أو التليفزيوني أو الإذاعي، وهي من العناصر الأساسية في صناعة الفيلم السينمائي أو المسرحية، وقد سبقت الموسيقى التصويرية على الحوار في الأفلام الصامتة في فجر صناعة السينما العالمية والتي أبرزها هي أفلام شارلي شابلن فنظرا لعدم توافر تكنولوجيا الصوت في ذلك الوقت، كان يتم التعبير عن المشاهد من خلال عرض الفيلم الصامت على الشاشة ويقوم الموسيقي أو عازف البيانو بعزف المقطوعات التي تناسب المشاهد المختلفة. تكون هذا البحث من: مشكلة البحث، أهداف البحث، أسئلة البحث، عينة البحث، منهج البحث، أدوات البحث، مصطلحات البحث. أما الإطار النظري للبحث فيتضمن: 1-الدراسات السابقة المرتبطة بموضوع البحث. 2-ثم نبذة عن حياة جون ويليامز. 3-التوزيع الأوركسترالي. 4-نبذة بسيطة عن الموسيقى التصويرية. الجزء الثاني تطبيقي ويشمل: • إجراء دراسة تحليلية وصفية لعينة البحث وتناولها بالتحليل النظري والهارموني. • نتائج البحث وتفسيرها.
John Towner Williams (born February 8, 1932) is an American composer, conductor, and pianist. Widely regarded as one of the greatest film composers of all time, he has composed some of the most popular, recognizable, and critically acclaimed film scores in cinematic history in a career spanning over six decades. Williams has won 24 Grammy Awards, seven British Academy Film Awards, five Academy Awards, and four Golden Globe Awards. With 51 Academy Award nominations, he is the second most-nominated individual, after Walt Disney. Harry Potter and the Philosopher's Stone, on 26 June 1997, the books have found immense popularity, critical acclaim and commercial success worldwide. They have attracted a wide adult audience as well as younger readers and are often considered cornerstones of modern young adult literature. [2] As of February 2018, the books have sold more than 500 million copies worldwide, making them the best-selling book series in history, and have been translated into eighty languages. [3] The last four books consecutively set records as the fastest-selling books in history, with the final instalment selling roughly eleven million copies in the United States within twenty-four hours of its release. In movie industry terminology usage, a sound track is an audio recording created or used in film production or post-production. Initially the dialogue, sound effects, and music in a film each has its own separate track (dialogue track, sound effects track, and music track), and these are mixed together to make what is called the composite track, which is heard in the film. A dubbing track is often later created when films are dubbed into another language. This is also known as a (M & E) track (music and effects) containing all sound elements minus dialogue which is then supplied by the foreign distributor in the native language of its territory. The research includes Introduction - research problem - Research objectives - the importance of research - research questions - Sample Search - Research Methodology - search tools - search terms. The research is divided into two parts: The first part, theoretical, includes: 4- Previous studies. 5- John Williams'. 6- The orchestration. 7- Sound track. The theoretical framework for research includes: A simple overview of the soundtrack. Then a brief account of John Williams' life and his style of orchestral distribution by analyzing the blog (Hedwig's Theme) from the Harry Potter movie. (Harry Potter) Then conclude with references and recommendations. The practical framework includes: 1 - Conducting an analytical and descriptive study of the research sample and dealing with it in theoretical and hormonal analysis. 2 - Research results and their interpretation.
Keywords: التوزيع الأوركسترالي -- وليامز، جون -- الموسيقى التصويرية